2008
DOI: 10.1073/pnas.0711219105
|View full text |Cite
|
Sign up to set email alerts
|

Paternal effects on offspring fitness in a multimale primate society

Abstract: When females mate with multiple males, paternal care is generally expected to be negligible, because it may be difficult or impossible for males to discriminate their own offspring from those of other males, and because engaging in paternal care may reduce male mating opportunities. Consequently, males in multimale societies are not predicted to provide direct benefits to their offspring. We have recently demonstrated, however, that males in a typical multimale primate society (yellow baboons, Papio cynocephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 47 publications
4
88
1
1
Order By: Relevance
“…Although male mandrills exhibit little parental care, sire-offspring dyads show more affiliation than dyads consisting of a male and an unrelated infant (Charpentier et al, 2007), and possible sires protect infants and juveniles aggressively during annual captures (Setchell, unpublished observations). Studies of baboons, a closely-related species also characterized by a multi-male, multi-female mating system, have shown that the presence of the sire enhances offspring fitness (Charpentier et al, 2008), suggesting that paternal influences on offspring success may be more prevalent than previously supposed.…”
Section: So Why Are Mandrills Red?mentioning
confidence: 94%
“…Although male mandrills exhibit little parental care, sire-offspring dyads show more affiliation than dyads consisting of a male and an unrelated infant (Charpentier et al, 2007), and possible sires protect infants and juveniles aggressively during annual captures (Setchell, unpublished observations). Studies of baboons, a closely-related species also characterized by a multi-male, multi-female mating system, have shown that the presence of the sire enhances offspring fitness (Charpentier et al, 2008), suggesting that paternal influences on offspring success may be more prevalent than previously supposed.…”
Section: So Why Are Mandrills Red?mentioning
confidence: 94%
“…Paternal effects play a large role in the development of widely different animals such as fruit flies (Fitch et al, 1998), mice (Chong et al, 2007), non-human primates (Charpentier et al, 2008) and humans (Tesarik et al, 2002), and thus are crucial to the developmental trajectory of an organism. Paternal factors, such as mRNAs contained in spermatozoa, have been implicated in the regulation of cleavage during embryogenesis.…”
Section: Paternal Effects In Epigeneticsmentioning
confidence: 99%
“…It is clear that a number of key traits develop during the course of human evolution, which alter the fundamental structure of society. In practice, these are underpinned by unique mechanisms associated with human cultural capacities, but, at a socioecological level, these are properties found elsewhere in the animal kingdom, and therefore can be considered to have evolved as behavioural traits in response to resource-based conditions-the massive extension of a fission-fusion system (elephants, Loxodonta africana) (Couzin 2006); much greater substructuring within multi-male, multi-female communities (hamadryas baboons, Papio hamadryas) (Kummer 1968); strong and persistent male-female relationships (many birds, for example) (Mock & Fujioka 1990); higher levels of paternal investment (primates, many birds) (Charpentier et al 2008); and larger group sizes (Janson & Goldsmith 1995).…”
Section: Derived Human Social Patternsmentioning
confidence: 99%